«BUILDING – BASE» SYSTEM BOUNDARY DEFORMATIONS EXCEEDING PROBABILISTIC ESTIMATION METHODOLOGY (Academic journal Industrial Machine Building Civil Engineering, 2017)
In the paper the method is proposed and the algorithm is developed for solving the problem of «building – base» system exceeding boundary deformations in reliability parametric theory framework probability (risk) determination. For calculations, the method of statistical tests (Monte-Carlo) was used. Using the powerful Mathcad complex, the computer program has been developed to implement the proposed calculation method has been developed. The calculations of the existing «building-base» system have been performed from determination of this system exceeding boundary deformations probability (risk). Analysis of the probability calculation indicates the need to improve existing approaches to determination the probability of deformations exceeding boundary value, because new methods will increase the reliability of solving geotechnical problems.
Keywords: probability; system reliability theory; statistical test method; distribution function of random variable distribution; «building – base» system; deformation of the base; calculation of deformations by the method of layer summing